Ghi nhận hình ảnh cắt lớp 3 chiều sử dụng hiệu ứng dịch chuyển pha Doppler với nguồn sáng phổ rộng - Duc, Quang Pham (2025)
In this study, the authors proposed a new method that allows the reconstruction of three-dimensional (3D) tomographic images of an object using a broadband light source. The frequency of the reference wave was modulated by Doppler’s effect due to the movement with a constant velocity of the reference mirror. The variation of the interference light intensity caused by Doppler’s effect at the position of each pixel of the camera was characterised by the light intensity function and this function was sampled by a very high frame rate camera. Applying the band-pass filter and inverse Fourier transform to the spectrum of the intensity function allowed reconstructing the 3D image of the object with very high resolution.